An Investigation into risk management within the banking industry: Have attitudes changed since the subprime mortgage crisis? - Pettit, Michael (2011)
ABSTRACT With the global economy left in shatters after the events of the subprime mortgage crisis, the general public is left looking for answers as to how such a catastrophe could possibly have happened. Whilst the blame does not fall entirely on the banks, their negligent approach to risk management was a major factor. As the world strives to rebuild its economies, a change in attitude is needed by the banks to prevent a repeat of the events that caused the financial crisis. Focusing on the risk disclosures of four UK based banks and one Spanish bank, this dissertation aims to discover whether banks are improving their approach to risk management. This is done through a content analysis of the annual reports straddling a time-line surrounding the financial crisis. The analysis leads to the conclusion that risk attitudes have been improving since the crisis but there is still much room for improvement, especially with regard to liquidity risk management, which was a key factor in the huge capital losses suffered by the banks.